The Influence of Leadership, Work Commitment and Organizational Culture on Employee Performance at the Bank SulutGo Limboto - Tomy Gobel; Titin Dunggio; William Indra S. Mooduto (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This research was conducted at the Bank Sulutgo Limboto in November 2020. With the aim of research to determine the influence of leadership, organizational culture, work commitment on employee performance at the Bank Sulutgo Limboto. This research was traced using multiple linear regression analysis method. The research location chosen was the Limboto Branch of Bank SulutGo in Gorontalo Regency and was carried out around October-November 2020. The study population was employees of Bank SulutGo Limboto branch with a total of 40 people. Sampling is done by means of saturated samples or census because the number of employees is 40 people so all of them are taken to represent research information. As for the research components to be studied are the dependent variable / dependent variable (performance of Bank SulutGo employees), and the independent variables / independent variables are (leadership, organizational culture, and work commitment). Primary data collection techniques by means of observation, interviews, and surveys using multiple regression analysis. The results showed that there was a positive influence between leadership on employee performance of 3.103> 0.685 and p value of 0.004 <0.005, work commitment had an effect on the performance of Bank Sulutgo employees of 3.171> 0.685 and p value of 0.003 <0.005 and organizational culture had an effect on the performance of employees of Bank Sulutgo Limboto is 3.053> 0.685 and p value 0.004 <0.005, simultaneously the three variables contribute positively on the employees performance of the Bank Sulutgo Limboto based on the F-count value (20.430) greater than the F-table value (2.863) and p value 0.000 < 0.005.